IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE Two Stay Two Stray (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 5 SUNGAI SELARI KECAMATAN BUKIT BATU - Yusmarni Yusmarni; lazim.n lazim.n; Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the poor results of students' mathematics learning, with an average grade 57.92. Among students who totaled 24 people only 7 students who completed KKM with classical completeness reach 29.16%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes Mathematics Elementary School fifth grade students 5 Selari River Bukit Batu subdistrict by applying cooperative learning model type Two Stay Two Stray (TSTS). Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the increase in the number of students who reach the KKM of 7 people (29.16%) on the base score to 10 people (41.66%) in the first cycle and increased to 23 people (95.83%) in the second cycle. This means that the sample classes have been completed in the classical. An increase in the average learning outcomes of basic score is 57.92 into 63.54 and 76.88 in the first cycle in the second cycle. An increase in the activity of the teacher. At the first meeting of the first cycle of activity percentages of teachers is 58.33%, the second meeting 75%. While the second cycle the first meeting with the percentage of 83.33%, and the second meeting increased 91.67%. While the student activity also increased that the first meeting of the first cycle of the percentage of student activity is 58.33%, 70.83% second meeting, the first meeting of the second cycle of 79.17% and a second meeting fixed with an average 91.67%. Results of the study in class V SDN 5 Sungai Bukit Batu subdistrict Selari prove that the implementation of cooperative learning model type Two Stay Two Stray (TSTS) can increase student learning outcomes Math class V SDN 5 Selari River Bukit Batu subdistrict.Keywords: Cooperative type Two Stay Two Stray, mathematics learning outcomes